INOVASI BAHAN AJAR PAI BERBENTUK TABLOID/CETAK - Rafizal (Postgraduate Program UIN Sultanah Nahrasiyah Lhokseumawe, 2025)
This journal presents the results of a study on innovative development of Islamic Religious Education (PAI) teaching materials in the form of printed tabloids, in response to the evolving needs of education. These materials are designed to create an engaging and interactive learning experience, encouraging active student participation. The research involved several stages, including needs analysis, content design, and trials at various educational levels. The findings show that tabloid-based teaching media can enhance students’ learning interest, understanding, and material retention. Data collected through questionnaires and interviews with students and teachers indicate that this material effectively creates a dynamic learning atmosphere and accommodates diverse student characteristics. These findings highlight the importance of innovation not only in academic content but also in delivery methods, with tabloid-format materials offering a practical solution to improving the quality of PAI learning in the modern era.